Mediation As a Non- Litigation Effort in Settlement Dispute Land in Indonesia - Nurwidiatmo (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Land is something the needs required by each Indonesian citizens. Land is the basic capital development. in life socialize in general hang his life on the benefit land and have relationship that is eternal with the state and the people. Therefore That law agrarianism in Indonesia in general general has arranged in Constitution Number 5 of 1960 concerning Basic Rules of Procedure Agrarian Law (UUPA), which is implementation (formel gesetz) Article 33 paragraph 3 of the 1945 Constitution which states that